The modulatory effect and implication of gut microbiota on osteoporosis: from the perspective of "brain–gut–bone" axis. Issue 13 (28th May 2021) - Zhang, Yuan-Wei; Li, Ying-Juan; Lu, Pan-Pan; Dai, Guang-Chun; Chen, Xiang-Xu; Rui, Yun-Feng
Abstract : The "brain–gut–bone" axis is related to osteoporosis and can be a potential target for the prevention and treatment of it. The "brain–bone", "gut–bone" and "brain–gut" connections are all closely relevant between the gut microbiota and osteoporosis. Abstract : Osteoporosis (OP) is a kind of systemic metabolic disease characterized by decreased bone mass and destruction of the bone microstructure. In recent years, it has become an expected research trend to explore the cross-linking relationship in the pathogenesis process of OP so as to develop reasonable and effective intervention strategies. With the further development of intestinal microbiology and the profound exploration of the gut microbiota (GM), it has been further revealed that the "brain–gut" axis may be a potential target for the bone, thereby affecting the occurrence and progression of OP. Hence, based on the concept of "brain–gut–bone" axis, we look forward to deeply discussing and summarizing the cross-linking relationship of OP in the next three parts, including the "brain–bone" connection, "gut–bone" connection, and "brain–gut" connection, so as to provide an emerging thought for the prevention strategies and mechanism researches of OP.